A history of England. Volume 1, Prehistory to 1714 - Bisson, Douglas R., 1954-; Roberts, Clayton, 1923-2018; Roberts, David, 1923-2016 (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"The seventh edition of this two-volume narrative of English history draws on the most up-to-date primary and secondary research, encouraging students to interpret the full range of England's social, economic, cultural, and political past from its first inhabitants to the 2020s. A History of England, Volume 1: Prehistory to 1714 focuses on the key social, economic, cultural, environmental, intellectual, and political events and themes of English history through the early 18th century. Topics include the Viking and Norman conquests of the 11th century, the creation of the monarchy, the Reformation, and the Glorious Revolution of 1688. The text discusses events in Scotland, Wales, and Ireland as they affected developments in England. There is a new section dealing with the decline of belief in witchcraft. This book is essential introductory reading for students of the history of England and Britain"--
Keywords: Great Britain -- History; England -- Civilization; HISTORY / Europe / Great Britain